Meningkatkan Kemampuan Membedakan Jenis Perkembangbiakan Hewan Menggunakan Media Pop-Up Book Digital pada Anak Gangguan Spektrum Autisme - Laila Safitri; Rahmahtrisilvia Rahmahtrisilvia; Antoni Tsaputra; Endang Sri Handayani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyse the effectiveness of using digital pop-up books in improving the ability of pupils with Autism Spectrum Disorder (ASD) to distinguish between different types of animal reproduction. This study employed a Classroom Action Research (CAR) approach, conducted over two cycles, each comprising the stages of planning, implementation, observation and reflection. The research subjects consisted of two Year 10 students at the Mandailing Natal State Special School. Data collection techniques included learning outcome tests, observation of student activities, and documentation. Data analysis was conducted using quantitative descriptive methods to determine the percentage increase in students’ abilities in each cycle, as well as qualitative descriptive methods to describe changes in learning behaviour during the learning process. The research results indicate a gradual improvement in the students’ abilities. Initially, the students’ abilities were still low, at 43.75% and 31.25%. Following the intervention in Cycle I, abilities improved to 62.50% and 59.38%, though they had not yet met the mastery criteria. A significant improvement occurred in Cycle II, with achievement levels of 90.63% and 84.38%, which fell into the ‘very good’ category. In addition to improving learning outcomes, the Digital Pop-up Book medium also enhanced students’ attention, engagement, and independence in learning